Unsupervised online neuropsychological test performance for individuals with mild cognitive impairment and dementia: Results from the Brain Health Registry. Issue 1 (21st June 2018) - Mackin, R. Scott; Insel, Philip S.; Truran, Diana; Finley, Shannon; Flenniken, Derek; Nosheny, Rachel; Ulbright, Aaron; Comacho, Monica; Bickford, David; Harel, Brian; Maruff, Paul; Weiner, Michael W.
Abstract: Introduction: The purpose of this study is to compare online neuropsychological test performance of older adults across self‐reported diagnoses of being cognitively normal, mild cognitive impairment, and dementia due to Alzheimer's disease and to determine the association of memory concerns and family history of dementia on cognitive performance. Methods: Participants completed the Cogstate Brief Battery unsupervised at home. Results: Data from 6463 participants over the age of 55 years were analyzed. Adults with the diagnosis of mild cognitive impairment and Alzheimer's disease were associated with poorer performance on all cognitive tests than cognitively normal adults ( P  < .05 for all), and online cognitive test performance significantly improved diagnostic classification ( P  < .001). Poorer performance on all cognitive measures was associated with memory concern ( P  < .001 for all) but not family history of dementia. Discussion: Our results provide preliminary support for the use of cognitive tests taken online without supervision as a means to improve the efficiency of participant screening and recruitment for clinical trials.